ENVIRONMENTAL AWARENESS THROUGH ENVIRONMENTAL SELF-APPLICATION STUDY (KAKAS) - Haji Iksan, Zanaton; Syed Zakaria, SharifahZarina; AzizahSamsuddin, Noor (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractEnvironmental knowledge alone does not guarantee a positive behaviour towards the environment in the absence of awareness and appreciation for the environment. The question is, how to raise environmental awareness?Thus, this study aims to instil environmental awareness throughEnvironmental Self-Application Study (KAKAS). The study was conducted on 27 graduate students who are school teachers. The participants conducted KAKAS activities throughout one semester. Kakas was run through six steps, namely 1) Identifying wasteful practices in everyday life, 2) Planning self-study that can solve the problem in step 1, 3) Conducting independent scientific and systematic research according to their creativity, 4) Data collected â¥ 3 times with proofs 5) Sharing of independent research through poster presentations, 6) Summarizing the results of the impact study of environmental sustainability in everyday life.Each of the study participants were asked to reflect on the activities that has been done throughout the semester. The study found that KAKAS activities has been able to: 1) increase participants environmental awareness through the awareness on waste, 2) impress the participants for these activities could contribute to the environment, 3) increase concerns for the environment, 4) increase responsibility towards the environment, 5) instil awareness of the needs for conserving natural resources, 6) each individual is able to give contribution to the environment, 7) environmental care as a sign of gratitude to the Creator.KAKAS brings implications on environmental awareness which in turn can lead to the appreciation and positive action on the environment. This is important to be instilled in teachers because they are role models to students. Hopefully, this awareness can be delivered to their students throughout their studies.key Words: environmental awareness, reflection, teachersâ awareness, self-study